1990
DOI: 10.1155/1991/91729
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relationship Between T15 and J558 Idiotypes in BALB/c Mice

Abstract: In inbred strains of mice, antiphosphorylcholine (PC) and anti-czl,3 dextran (DEX). antibodies are structurally distinct from each other and have been shown to exhibit noncrossreactive antigen binding and idiotypic specificities. However, the prototype anti-PC and anti-DEX antibodies, TEPC15 and J558, respectively, were shown to be connected via a common autoantiidiotypic monoclonal antibody isolated from newborn BALB/c mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…There is evidence supporting a role for B cell idiotypic interactions early in life that modulate the development of B cell clones responsive to DEX and to other T-independent antigens (56, 57). Neonatal injection of the anti-PC antibodies, such as the T15 antibody that is presumably more abundant in TdT−/− mice, leads to a reduction in J558 idiotype expression when these mice were immunized with DEX as adults (58). Therefore, the mechanism by which J558 Id expression requires TdTS may be indirect and involves the selection of J558-expressing clones as a result of B cell interactions with other B cells or other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence supporting a role for B cell idiotypic interactions early in life that modulate the development of B cell clones responsive to DEX and to other T-independent antigens (56, 57). Neonatal injection of the anti-PC antibodies, such as the T15 antibody that is presumably more abundant in TdT−/− mice, leads to a reduction in J558 idiotype expression when these mice were immunized with DEX as adults (58). Therefore, the mechanism by which J558 Id expression requires TdTS may be indirect and involves the selection of J558-expressing clones as a result of B cell interactions with other B cells or other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…These non-T15 antibodies also failed to confer prOtective immunity in recipient XID mice against virulent S. pneumoniae. We have further reported in a separate study that mice primed with R36A 2 days after birth also fail to respond to a structurally distinct but idiotypically linked antigen c1,3 dextran (Vakil and Kearney, 1991 Kearney, 1991). Therefore, the dominant expression T15 / B cells .…”
Section: Introductionmentioning
confidence: 84%
“…We have employed a modification of this assay (Hurwitz et al, 1982) We have previously reported the stimulatory effects of the anti-T15 antibody BD2 and the antianti-T15 antibody DB3, products of perinatal B-cell hybridomas (Bast et al, 1984; (Vakil and Kearney, 1991 Etlinger and Heusser, 1986), despite the ubiquitous nature of PC antigen,in the latter (Potter,, 1977 Chang et al (1984). These non-T15 antibodies also failed to confer prOtective immunity in recipient XID mice against virulent S. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible problem with early vaccination of mice with polysaccharides may come from deleterious modulation of the murine antibody response (46,129,130). This effect is well demonstrated by the response to phosphocholine (PC).…”
Section: Immunogenic Considerations For Conjugate Vaccinesmentioning
confidence: 99%
“…In spite of these concerns, it must be pointed out that millions of infants have been immunized at 3 months of age with the H. influenzae group B polysaccharide-protein conjugate vaccines and there have been no reports of deleterious immunologic or developmental effects. For a pneumococcal vaccine, however, five or more different conjugates would be required, possibly increasing the risk of deleterious consequences, especially if they are dependent on idiotype network interactions that may interfere with B-cell differentiation (46,130).…”
Section: Immunogenic Considerations For Conjugate Vaccinesmentioning
confidence: 99%